2010
DOI: 10.29333/ejgm/82842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Breast Size on Lung Function

Abstract: Aim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…While, in Turhan-Haktanır et al, study, they depended on the effect of breast size on lung functions in different breast weights but not the effect after reduction mammaplasty. That was unreliable result in comparison to ours [10].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…While, in Turhan-Haktanır et al, study, they depended on the effect of breast size on lung functions in different breast weights but not the effect after reduction mammaplasty. That was unreliable result in comparison to ours [10].…”
Section: Discussioncontrasting
confidence: 79%
“…While some studies prove the positive effect of mammoplasty on the pulmonary function test [6,9], others deny this effect [5,10]. The debate extended between those who stated the beneficial effect of breast reduction surgery and how much this surgery improves the lung function and oxygen saturation, with others who had a contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in breast size could increase chest compliance, which interferes on pulmonary ventilation. Although Turhan-Haktanir et al 33 have observed no correlation between breast size and pulmonary function in a study performed with 100 healthy volunteers women, some previous studies have suggested the improvement in breathing following bilateral breast reduction in cases of macromastia [34][35][36] . Besides macromastia, pulmonary function tests may be affected by patient weight.…”
Section: Discussionmentioning
confidence: 89%
“…Besides macromastia, pulmonary function tests may be affected by patient weight. Indeed, as hypothesized by Turhan-Haktanir et al 33 , macromastia associated with obesity may lead to a relative restriction in chest wall compliance, so breast size reduction is supposed to enhance chest wall compliance and lead to improved ventilation. However, a post-hoc analysis showed no correlation between the pulmonary variables and the BMI of the participants of the present study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation